Issues and Challenges in Cultivating Environmentally Preferred Purchasing Among Young Generation - Abidin, Rahimi; Mohd Zahari, Fadhilah; Osman, Nor Hasni; Ahmad, Azhar; Anwar, A; Achiraewati, Eri; Nu’man, A H (Akademia Baru, 2022)
Purchase and use of environmentally preferable product can have a profound impact to improved ability to meet existing environmental sustainability goals.This article presents a study which examine the issues and challenges in cultivating environmentally preferred purchasing (EPP) among young generation. A survey has been conducted in which the respondents are staff and students of one of public university in Malaysia. A set of questionnaires was used for data collection of the study. Data from 324 respondents was analyzedusing a descriptive and inferential analysis in fulfilling the research objectives. The study found that the factors which have significant effect on the EPP practices are the awareness, promotion, knowledge and attitudes. The findings of this study provide a great foundation for a better understanding of EPP practice among the Malaysian, particularly in the context of the educated young generation. The discoveries of this study also have a noticeable implication, especially for the government to increase the awareness and other practitioners to expand the values and promotion for green product and services